Trends in Insurance Status during Initial Presentation of Testicular Carcinoma: Examining Health Outcomes and Implications of Health Reform for Young Adults in the United States. Issue 1 (January 2019) - Chipollini, Juan; Tang, Dominic H.; Zhou, Junmin; Reich, Richard R.; Leone, Andrew R.; Gilbert, Scott M.; Sexton, Wade J.
Abstract: Introduction: We evaluated trends in insurance status, and assessed socioeconomic factors associated with clinically metastatic testicular cancer presentation and potential barriers to treatment in the United States. Methods: The National Cancer Database was queried for patients with testicular germ cell tumors diagnosed from 2004 to 2014. Temporal trends and forecast of insurance status were examined in the years before and after the ACA (Affordable Care Act) was enacted. Multivariable logistic regression was used to assess predictors of clinically metastatic presentation. Results: A total of 58, 348 patients were identified with 37.95% presenting with clinically metastatic disease. The uninsured rate remained relatively unchanged during the years before and after the ACA was enacted (11.7% vs 11.9%, respectively). Predictors for clinically metastatic presentation were Medicaid (OR 2.12, 95% CI 1.80–2.50), Medicare (OR 1.35, 95% CI 1.13–1.60) and uninsured status (OR 1.41, 95% CI 1.22–1.64) compared to privately insured patients. A forecast model revealed no significant changes in the uninsured rate (11.58% to 11.60%) for 2015 through 2017. Conclusions: Socioeconomic disparities continue to be barriers for young adults presenting with testicular cancer in the United States. Longer prospective followup will be required to assess the impact of payer status with the reportedly increased health coverage fostered by the ACA.